Pengaruh Sistem Pengendalian Intern, Kompetensi Sumber Daya Manusia dan Penerapan Sistem Akuntansi Keuangan Daerah Terhadap Pelaporan Keuangan Pemerintah Daerah Kab. Grobogan (Studi Persepsi Pegawai SKPD di Kabupaten Grobogan) - Galih Sudarsono; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
The purpose of this research to examine and analyze the influence of the internal control system, human resource competencies and application of local goverment financial accounting system to the information value of accounting entity financial..The questionnaires amounted to 57 distributed to all the chief financial officer on employees of local government units (SKPD) the local goverment of Grobogan regency. Data were collected using questionnaire survey. The data were processed using SPSS version 21.0. The multiple linear regression analysis was employed to test research hypotheses. The results of hypothesis testing show that the internal control system, human resource competencies and application of local goverment financial accounting system have significant positive effects on the information value of accounting entity financial reporting.